Current status on M. pneumoniae: Clinical Features and Management Strategies - Asit K; Bragadeeshwaran N; Janhavi MS; Shamina S; Lavanya SV; Suria P; Muthu PP (Ibom Medical Journal)
Background: The COVID-19 pandemic has significantly impacted Mycoplasma pneumoniae (MP), leading to a decline in prevalence and delayed resurgence. The rise of macrolide-resistant M. pneumoniae complicates treatment, necessitating alternative antibiotics.